HUMOR MASYARAKAT BELANTIK DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA - Isnan, Faisal (Diksi, 2020)
(Title: The Humor of the Belantik Society in the Novel "Orang Biasa" by Andrea Hirata). Andrea Hirata consistently tells stories about the values of local wisdom and current social issues in simple language. One of the languages used in his novel is humor. This study aims to describe the form of humor and to examine the sociocultural factors of the Belantik people in Andrea Hirata's novel (Ordinary People). The data were obtained by using baca-catat (reading and notetaking) technique. Data were analyzed qualitatively based on Berger's humor theory, especially categories and techniques of humor. The findings of this study show that there are two categories of humor in interpersonal relationship, such as language and logic. The techniques of language consist of satire, literalness, and insult; while the techniques of logic consist of absurdity, analogy, dan repetition. Generally, the humor contained in this novel occurs as a result of close interpersonal relationships, such as the illogical way of thinking of a character, the way a character speaks to another character, and the way in which social criticism is delivered through the humor.Keywords: humor, satire, social criticism, absurdity